A stability index for travelling waves in activator-inhibitor systems. Issue 1 (February 2020) - Cornwell, Paul; Jones, Christopher K. R. T.
Abstract: We consider the stability of nonlinear travelling waves in a class of activator-inhibitor systems. The eigenvalue equation arising from linearizing about the wave is seen to preserve the manifold of Lagrangian planes for a nonstandard symplectic form. This allows us to define a Maslov index for the wave corresponding to the spatial evolution of the unstable bundle. We formulate the Evans function for the eigenvalue problem and show that the parity of the Maslov index determines the sign of the derivative of the Evans function at the origin. The connection between the Evans function and the Maslov index is established by a 'detection form, ' which identifies conjugate points for the curve of Lagrangian planes.